Hydrophilic species in the composition of Herbarium Florae Rossicae exsiccatum at herbarium of Uman National University of Horticulture (UM) - Chorna, Galina A.; Mamchur, Tatyana V. (Experimental Biology and Biotechnology, 2019)
Results of processing of hydrophilic species from Herbarium Florae Rossicae (1897–1970) of the historical herbarium of Uman National University of Horticulture are presented (UM). It is found that hydrophilic taxa are represented by 160 species of 70 genera of 30 families of higher spore and angiospermous plants. Quantitative composition of exsiccate of individual collectors and territorial gathering are analyzed. It is found that hydrophilic types of territories in Latvia (collector K. Kupffer), North-West Russia, in particular, surroundings of St. Petersburg (collectors N. Purring and V. Andreev) are most fully represented. On the territory of Ukraine, gathering was made in surroundings of Kiev and Chernigiv region (collectors A. Rakoci and N. Zinger) and in surroundings of Kharkov (collector P. Nalyvaiko). We determined 40 hydrophilic species in the exsiccate composition which are now protected in many European countries. Aldrovanda vesiculosa presented by collections of the founders of exsiccate publication Herbarium Florae Rossicae S. Korzhinsky and A. Rakoci, as well as Caldesia parnassifolia (collectors A. Lorchenko and V. Finn) are now classified as species protected by the Bern Convention. Information on the floristic studies of A. Rakoci (1894 –1903) and P. Nalyvaiko (1891–1897) is presented. It is found that the habitats of the rarest hydrophilic species collected by them for exsiccate Herbarium Florae Rossicae are now lost, so that these samples published more than 100 years ago acquire a memorial value. It is determined that the Cyperaceae family is most fully represented in the exsiccate composition.